2019
DOI: 10.7567/1347-4065/ab19a6
|View full text |Cite
|
Sign up to set email alerts
|

Unoccupied conduction band of chloroaluminum phthalocyanine

Abstract: The electronic structure of the unoccupied conduction band of polycrystalline chloroaluminum phthalocyanine was investigated by X-ray absorption spectroscopy (XAS) near the Cl K-edge. XAS spectra were recorded in total electron yield (TEY) and partial Auger electron yield (AEY) modes. Partial AEY spectra were measured using normal and spectator Cl KL 2,3 L 2,3 Auger yields as a function of photon energy. Although the TEY spectrum showed a broad shape; that was difficult to deconvolute curve fitting, the normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The analysis of the SP1 spectator shi parameters of the RAS spectra measured at these three photon energies shows that the electron delocalization degree of electron excited of p* symmetry (2471.9 eV) and s* (2474.4 eV) states is higher for P3HT/ITO than P3HT/Fe-MWCNT-5%. This s* transition presents a transition moment perpendicular to the polymer backbone, as previously discussed by H. Ikeura-Sekiguchi et al 55 and R. Onoki et al 57 However, at photon energy corresponding to the resonance maximum (2473.2 eV) the electron delocalization degree is higher for the P3HT/Fe-MWCNT-5% nanocomposite compared to P3HT/ITO. These results show that the electronic coupling between P3HT and Fe-MWCNT depends on the character of the electronic excited states.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The analysis of the SP1 spectator shi parameters of the RAS spectra measured at these three photon energies shows that the electron delocalization degree of electron excited of p* symmetry (2471.9 eV) and s* (2474.4 eV) states is higher for P3HT/ITO than P3HT/Fe-MWCNT-5%. This s* transition presents a transition moment perpendicular to the polymer backbone, as previously discussed by H. Ikeura-Sekiguchi et al 55 and R. Onoki et al 57 However, at photon energy corresponding to the resonance maximum (2473.2 eV) the electron delocalization degree is higher for the P3HT/Fe-MWCNT-5% nanocomposite compared to P3HT/ITO. These results show that the electronic coupling between P3HT and Fe-MWCNT depends on the character of the electronic excited states.…”
Section: Resultssupporting
confidence: 65%
“…Comparing S 1s NEXAFS spectra of regioregular P3HT lm and polycrystalline powder (RR-P3HT) it was shown a reduction in the LUMO energy level which the authors suggested as being directly associated to the p-p intermolecular interaction present for the regioregular polymeric lm. 55 This would explain the remarkable signal related to the p* transition well visualized in the spectrum of Fig. 1c for pristine P3HT, which also demonstrate the quality of the lm deposition.…”
Section: Resultsmentioning
confidence: 68%